Exploring Moroccan EFL Teachers' Engagement in a WhatsApp Professional Development Group: Benefits and Concerns: Benefits and Concerns - Raha, Yassine; Mima, Walid; Mohamed, Benmhamed (International Journal of Linguistics and Translation Studies, 2023)
This study explores the involvement of Moroccan EFL teachers in a WhatsApp group called "Professional Development" and their perceptions of online communities, particularly WhatsApp, concerning their professional development. Through a combination of WhatsApp group observation and semi-structured interviews, 20 EFL teachers from diverse locations across Morocco were engaged. The data collected were analyzed thematically. The findings reveal that WhatsApp serves as a valuable platform for teachers to access teaching materials such as tests, quizzes, PDF books, and official circulars from the Ministry of Education. Additionally, 71.4% of the participants emphasize the significance of virtual communities for their professional development. However, 28.6% of the teachers express concerns about WhatsApp being a waste of time due to the sharing of irrelevant content and chaotic discussions that divert the group from its primary purpose.